In search of meadowlarks : birds, farms, and food in harmony with the land - Marzluff, John M. (Yale University Press, 2020)
An ornithologist's personal look at farming practices that finds practical solutions for sustainable food production compatible with bird and wildlife conservation. With predictions of a human population of more than nine billion by the middle of this century and eleven billion by 2100, we stand at a crossroads in our agricultural evolution. In this clear and engaging yet scientifically rigorous book, wildlife biologist John M. Marzluff takes a personal approach to sustainable agriculture. He travels to farms and ranches across North and Central America, including a Nebraska corn and soybean farm, California vineyards, cattle ranches in Montana, and small sustainable farms in Costa Rica, to understand the unique challenges and solutions to sustainable food production. Agriculture and wildlife can coexist, he argues, if farmers are justly rewarded for conservation; if future technological advancements increase food production and reduce food waste; and if consumers cut back on meat consumption. Beginning with a look backwards at our evolutionary history and concluding with practical solutions for change that will benefit farmers and ranchers, Marzluff provides an accessible and insightful study for the ecologically minded citizen, farmer, rancher, or conservationist.